Objective Information Theory - Xu, Jianfeng; Wang, Shuliang; Liu, Zhenyu; Wang, Yashi; Wang, Yingfei; Dang, Yingxu (SpringerBriefs in Computer Science, 2023)
Objective Information Theory (OIT) is proposed to represent and compute the information in a large-scale complex information system with big data in this monograph. To formally analyze, design, develop, and evaluate the information, OIT interprets the information from essential nature, measures the information from mathematical properties, and models the information from concept, logic, and physic. As the exemplified applications, Air Traffic Control System (ATCS) and Smart Court SoSs (System of Systems) are introduced for practical OITs. This Open Access book can be used as a technical reference book in the field of information science and also a reference textbook for senior students and graduate ones in related majors.